FTO 유전자 다형성이 복합운동에 따른 비만남자대학생들의 혈중지질 및 사이토카인에 미치는 영향 - 김용규; 이경희; 이채산 (Exercise science (Seoul, Korea), 2013)
본 연구는 체질량지수 27 이상의 비만남자대학생의 유전자 다형성 유형, AA+AT 유전자 집단(n=10), TT 유전자 집단(n=12)을 독립표집 하였다. 12주간의 50~70 %여유심박수의 유산소성 운동과 60~70 % 최대근력의 저항성 운동인 복합운동 수행이 중성지방, 저밀도지단백콜레스테롤, 고밀도지단백콜레스테롤 및 아디포넥틴, 인터루킨-6, 종양괴사인자-알파 농도의 변화에 미치는 효과를 규명하는 것이었다. 중성지방, 저밀도지단백콜레스테롤 농도는 처치 12주에 TT 유전자 집단이 AA+AT 유전자 집단보다 운동처치 기간이 증가됨에 따라 유의하게 감소하였으며(p<.05), 반면 고밀도지단백콜레스테롤 농도는 유의하게 증가하였다(p<.05). 아디포넥틴 농도는 TT 유전자 집단이 AA+AT 유전자 집단보다 운동처치 기간이 증가됨에 따라 유의하게 증가하는 것으로 나타났다(p<.05). 인터루킨-6 농도는 AA+AT 유전자 집단이 TT 유전자 집단보다 운동처치 기간이 증가됨에 따라 유의하게 증가하는 경향을 나타냈다(p<.05). 종양괴사인자-알파 농도는 TT유전자 집단이 AA+AT유전자 집단보다 운동처치 기간이 증가됨에 따라 유의하게 감소하는 경향을 나타냈다(p<.01). 결론적으로, 비만에 대한 운동처치 시 FTO유전자 다형에 따른 변이를 고려해야 되고, 운동강도 조건 등 더 폭 넓은 연구가 이루어져야 할 것으로 생각된다. The purpose of this study is to investigate the effects of combined exercise program on blood lipids and cytokine according to fat mass and obesity associated gene(FTO gene) polymorphism in the obese male college students for 12 weeks(4 days/week, 60 min/day). The subjects when it is performed submaximal exercise with 50~70 % heart rate reserve(50~70 % HRR) as Karvonen and Kuramoto & Payne method. Male college students of body mass index>27(BMI>27) at W university located in I city were selected as subjects. The subjects were divided into the two groups；a AA+AT gene allele(10 students) and a TT gene allele(12 students). The variables in blood lipids and cytokine were analyzed by two-way ANOVA with repeated measure(SPSS win ver. 11.5). The change of the triglyceride(TG) and the low density lipoprotein-cholesterol(LDL-C) were lower significantly in TT gene group than AA+AT gene group as the exercise treatment period(p<.05), but the high density lipoprotein-cholesterol(HDL-C) was higher in TT gene group than AA+AT gene group as the exercise treatment period(p<.05). The change of the adiponectin was higher significantly in TT gene group than AA+AT gene group as exercise treatment period(p<.05), but the interleukin-6(IL-6) was higher in AA+AT gene group than TT gene group as exercise treatment period(p<.05). The change of the tumor necrosis factor-α(TNF-α) hormone was lower significantly in TT gene group than AA+AT gene group as the exercise treatment period(p<.01). KCI Citation Count: 6